The relationship between psychological well-being and existential anxiety among university students in the industry 4.0 era - Makmuri, Tarsono; Hanifah, Abu; Nurjanah, Rita; Lisnawati, Unung; Zandi, Ahmad Sahira (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
Existential anxiety is a growing concern among university students, especially amid academic pressure and uncertainty about the future in the era of the Industrial Revolution 4.0. Research linking existential anxiety to psychological well-being based on Carol Ryff’s theory remains limited. This study aims to examine the relationship between psychological well-being and existential anxiety among university students through the lens of Ryff’s dimensions and Yalom’s concept of existential anxiety. The study adopted a quantitative method and involved 45 fifth-semester students at STIT At-Taqwa Ciparay, Bandung. Data were collected using validated scales and analyzed with the Pearson’s correlation through SPSS version 26. Results showed a significant negative correlation between psychological well-being and existential anxiety. Students with higher psychological well-being reported lower existential anxiety. These findings highlight the need to strengthen psychological well-being as a preventive approach to existential anxiety. The study contributes to educational psychology and supports mental health initiatives in higher education